Optimization Studies on the Changeable Components of Hydroelectric Power Plants - Tuna, Cihat; Aydın, Alp Buğra (My University, 2023)
The design flow rate, the dimensions of the transmission structure and the penstock size have a large impact on the cost of run-of-river type hydroelectric power plants. Equipment costs constitute a large part of the total budget of the plant. Optimum sizing, which maximizes the use of hydraulic potential, does not fit together with optimum sizing, which is necessary to obtain economic benefit from its investment. The main design parameters can be selected with the help of an optimization study in terms of both economic benefit and hydraulic potential. In this study, an easy to implement model, aimed at determining the costs associated with the different components in the structural organization of a hydroelectric power plant, is developed by a feasibility study to overcome the difficulties in practice. Gokcekoy HEPP, built in Turkey, was selected as the system. Annual energy production values were calculated by taking into account the current energy market conditions in Turkey. In addition, real situation studies were carried out regarding design flow rate selection, forced pipe diameter optimization and transmission channel sizing.
Keywords: Optimization; investment cost; Hydroelectric power plants; changeable components